2009
DOI: 10.1111/j.1749-6632.2009.05066.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Early Markers of Alzheimer's Disease using Quantitative Multiplex Proteomic Immunoassay Panels

Abstract: Alzheimer's disease (AD) is a debilitating neurodegenerative disorder with incidence expected to increase four-fold over the next decade. Extensive research efforts are focused upon identifying new treatments, and early diagnosis is considered key to successful intervention. Although imaging and cerebrospinal fluid biomarkers have shown promise in identifying patients in very early stages of the disease, more noninvasive cost-effective tools have remained elusive. Recent studies have reported that an 18-analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 49 publications
1
91
2
1
Order By: Relevance
“…We did not succeed in replicating the promising results of the earlier study with one exception. In our study we found lower CCL5 expression in AD, which was congruent with the initial study (6), but not with both other studies (10,11). The CCL5 gene is one of several C-C motif cytokine genes clustered on the q-arm of chromosome 17.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We did not succeed in replicating the promising results of the earlier study with one exception. In our study we found lower CCL5 expression in AD, which was congruent with the initial study (6), but not with both other studies (10,11). The CCL5 gene is one of several C-C motif cytokine genes clustered on the q-arm of chromosome 17.…”
Section: Discussionsupporting
confidence: 82%
“…Our results did not provide affirmative evidence for the results of this previously reported panel which showed 90% diagnostic accuracy for the differentiation of AD from controls (6). Two other groups also attempted to replicate the results of the 18-analyte multiplexed plasma panel, and obtained negative results as well, as is shown in Table 2 (10,11). One study showed no differences of protein levels between groups and poor diagnostic accuracy of the panel (11).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The earliest of these studies, by Ray et al [ 51 ] in 2007, used a sandwich ELISA immunoassay platform and identified an 18-analyte panel of proteins that segregated AD from controls. However, in an attempt at replication in another cohort (ADNI), by using seven of the analytes that gave a combined diagnostic accuracy of 90 % in the Ray et al [ 51 ] study, 61 % diagnostic accuracy was achieved, and the incorporation of a different 89-analyte panel increased this to 70 % [ 52 ]. These results, however, have been difficult to replicate [ 53,54 ].…”
Section: Multiplexingmentioning
confidence: 47%
“…Among them some hits are related to AD pathogenesis such as the apoE [195,196] as well as a broad range of inflammatory mediators [196,197]. In an array-based ELISA study, 18 signalling proteins were able to distinguish AD from control samples with high accuracy (90%) and to predict MCI to AD progression [198], although the validation of this dataset has been ambiguous [199,200]. The observation of a high variability between independent analyses indicates that further validations by independent methodologies in different cohorts need to be performed before resolving the clinical relevance of high-throughput blood-based analysis.…”
Section: Protein Biomarkersmentioning
confidence: 99%